2013
DOI: 10.1155/2013/492376
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Molecular Characterization ofEx VivoCultured Epiretinal Membrane Cells from Human Proliferative Diabetic Retinopathy

Abstract: Characterization of the cell surface marker phenotype of ex vivo cultured cells growing out of human fibrovascular epiretinal membranes (fvERMs) from proliferative diabetic retinopathy (PDR) can give insight into their function in immunity, angiogenesis, and retinal detachment. FvERMs from uneventful vitrectomies due to PDR were cultured adherently ex vivo. Surface marker analysis, release of immunity- and angiogenesis-pathway-related factors upon TNFα activation and measurement of the intracellular calcium dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 95 publications
(94 reference statements)
0
7
0
Order By: Relevance
“…The role of IAP in mediating diabetic retinopathy has received minimal analysis. One study showed that epiretinal membranes isolated from patients with proliferative retinopathy and maintained in culture contained cells that when exposed to high glucose increased their expression IAP and VEGFR2 further suggesting that IAP may be involved in the pathogenesis of this condition [43]. Thrombospondin-2 (TSP-2) is a protein that binds directly to IAP and enhances IAP-mediated cellular responses [44].…”
Section: Discussionmentioning
confidence: 99%
“…The role of IAP in mediating diabetic retinopathy has received minimal analysis. One study showed that epiretinal membranes isolated from patients with proliferative retinopathy and maintained in culture contained cells that when exposed to high glucose increased their expression IAP and VEGFR2 further suggesting that IAP may be involved in the pathogenesis of this condition [43]. Thrombospondin-2 (TSP-2) is a protein that binds directly to IAP and enhances IAP-mediated cellular responses [44].…”
Section: Discussionmentioning
confidence: 99%
“…The transcriptome analyses were largely in line with the abovementioned trends, and the protein expression in the vitreous humor confirmed those tendencies. It is well established that angiogenesis and fibrous proliferation are critical features of PDR, which can eventually lead to severe visual impairment [ 15 , 16 ]. On the one hand, the complex process of angiogenesis during PDR involves remodeling the vascular endothelial extracellular matrix, degradation of the basement membrane, and enhancement of endothelial cell invasion/migration [ 17 ], culminating in the formation of immature capillaries.…”
Section: Discussionmentioning
confidence: 99%
“…When it comes to cell death, the adenosine A2A receptor plays a role [17]. It has already been seen that blocking the A2A receptor controls microglial reactivity [18], delays excitotoxic death of embryonic motor neurons in vitro [19], and is able to prevent cell death in ischemic retinas [20]. This evidence makes it clear that this receptor is of great interest when it comes to therapeutic targets to improve the condition of various diseases in the retina and nervous system.…”
Section: Introductionmentioning
confidence: 99%